Documentation status socialization among Latinx immigrant parents. Issue 177 (25th May 2021) - Cross, Fernanda L.; Martinez, Saraí Blanco; Rivas‐Drake, Deborah
Abstract: Discriminatory legislation targeting Latinx immigrants in the United States has shifted how parents communicate with their children about the hostile political climate. One way that Latinx parents talk about and prepare their children to face prejudice is through ethnic‐racial socialization, which can promote children's positive development. Few scholars, however, have focused on how Latinx immigrant families with precarious documentation status socialize their children around issues of immigration, documentation status, and the potential for family separation. The current study seeks to broaden our understanding and conceptualization of ethnic‐racial socialization practices among Latinx immigrant families living in the United States to include documentation status socialization to better capture the messages parents transmit to their children about the causes and potential impacts of their documentation status. Thirty‐nine Latinx immigrant mothers aged 35–53 ( M = 41.66), (22 undocumented, 17 documented) were interviewed regarding the ways in which their documentation status informs their ethnic‐racial socialization practices. Five subthemes of Documentation Status Socialization were identified among both undocumented and documented parents. Example of subthemes included Limitations and Restrictions of Undocumented Status, and Documentation Privilege, in which parents discussed the limitation of being undocumented as well as the privilege that comes with the legal documentation status with their youth. Our findings yield important implications for practice and research alike.